PENYELESAIAN PERSELISIHAN KARYAWAN MELALUI MEDIASI (STUDI KASUS DI TOKO HOUSE OF CELENA ) - Ahmad Ashari; Novalinda Fajar Astari; Uswatun Hasanah (Universitas Trunojoyo Madura, 2018)
ABSTRACTMediation is the process of resolving the parties who are assisted by a neutral third party who does not take sides as a facilitator where the decision is taken based on the agreement of the parties to the dispute. This study aims to find out how to mediate between employees because of a conflict at the House Of Celena Store.In the House Of Celena Store there are conflicts including conflicts between employees and employees and different opinions between employees and managers. This research is the result of interviews about conflicts that occur between employees and employees and different opinions between employees and managers. As well as the factors that influence the harmony of industrial relations between superiors or owners of the House Of Celena ShopThe results of this study indicate that the strategies that managers do to mediate between hostile employees and the opinions between different managers and employees.